2009
DOI: 10.1186/1471-2407-9-381
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of breast cancer survival in two populations: Ardabil, Iran and British Columbia, Canada

Abstract: BackgroundPatterns in survival can provide information about the burden and severity of cancer, help uncover gaps in systemic policy and program delivery, and support the planning of enhanced cancer control systems. The aim of this paper is to describe the one-year survival rates for breast cancer in two populations using population-based cancer registries: Ardabil, Iran, and British Columbia (BC), Canada.MethodsAll newly diagnosed cases of female breast cancer were identified in the Ardabil cancer registry fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…The majority of cases were below the 50 years which have the same pattern with a number of studies (Mousavi et al, 2008;Yaghmaei et al, 2008;Sajadi et al, 2009;Najafi et al, 2013). Also, the reduction in the incidence of breast cancer in the elderly patients has been investigated in other studies (Tomatis et al, 1990).…”
Section: Discussionsupporting
confidence: 71%
“…The majority of cases were below the 50 years which have the same pattern with a number of studies (Mousavi et al, 2008;Yaghmaei et al, 2008;Sajadi et al, 2009;Najafi et al, 2013). Also, the reduction in the incidence of breast cancer in the elderly patients has been investigated in other studies (Tomatis et al, 1990).…”
Section: Discussionsupporting
confidence: 71%
“…It shows that the average age of patients will follow the same pattern. In two studies conducted in Iran the mean age of breast cancer diagnosis has been reported 61 years (Yaghmayee et al, 2007;Sadjadi et al, 2009). The low mean age of breast cancer diagnosis in Ardabil (nearly two decades) than these countries can be related to the low age of the cancer incidence in Ardabil province than developed countries or age in different races that confirms the necessity of planning and conducting extensive breast cancer screening programs for the lower age in Iran than other societies.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that only 17% of women conducted regular BSEs, and that 63% of women had never performed a BSE (Montazeri et al, 2008). Similarly, a study of Iranian women reported that BSE practices ranged from 3% to 17% (Sadjadi et al, 2009). In constrast, a study of 384 women in Taiwan found that 69% of the women had performed BSE, and that 24% of them had undergone mammography screening (Chiang et al, 2011).…”
Section: The Effects Of Education Program On Knowledge and Intention mentioning
confidence: 99%
“…Thus, in addition to low rates of regular BSE practices, studies also show that women lack knowledge regarding the importance of routine breast cancer screening. Breast cancer screening programs increase public awareness about the early detection of breast cancer (Sadjadi et al, 2009). Cognitive factors are thought to play important roles in the performance of BSEs.…”
Section: The Effects Of Education Program On Knowledge and Intention mentioning
confidence: 99%